Notes on Early Land Plants Today. 19. Validation of two names in Pellia (Pelliaceae, Marchantiophyta) - Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
When Schuster (1991) described Pellia endiviifolia subsp. alpicola and Pellia appalachiana he failed to state the herbarium where the types were deposited. Damsholt (2007) used the invalid name as a ‘basionym’ when elevating Pellia endiviifolia subsp. alpicola to a species without validating it.